Impact of polyethylene terephthalate nanoplastics (PET) on fibroblasts: a study on NIH-3T3 cells - Maria Elena Giordano; Francesca Lionetto; Maria Giulia Lionetto; Maria Giulia Lionetto (Frontiers in Physiology)
Plastic pollution has become a major environmental and public health issue due to rising global production. Nanoplastics (NPs) are especially concerning due to their widespread presence and potential health risks. This study aims to determine the impact of the exposure to polyethylene terephthalate (PET) NPs on fibroblast cells using the murine NIH-3T3 cells as experimental model. This is a relevant cellular model for several biological fields of application, including cell migration in wound healing and tissue regeneration. The PET NPs used represented an environmentally realistic PET NPs model since they were produced by a fast top down approach in a process close to the mechanical abrasion of microplastics occurring in the environment. They were characterized by an intrinsic autofluorescence which enables their use in studies of NPs interactions with biological systems without the need for additional fluorescent dyes. Additionally, the Hansen solubility parameters (HSP) of the PET NPs and the culture medium were determined to better understand their interaction. PET NPs were internalized by fibroblasts in a dose-dependent manner, localizing in the cytoplasm. While they caused only a slight reduction in cell viability (within 20% inhibition at 10–100 μg/mL) after 24 h exposure, they significantly impaired fibroblast migration, as demonstrated by the scratch assay, indicating possible interference in tissue repair. The exposure of the cells to PET NPs induced a significant dose-dependent ROS increase suggesting the induction of intracellular oxidative stress as possible mechanisms underlying the observed migration impairment. These findings highlight the potential risks of PET NPs to fibroblasts, emphasizing the need for further research into their impact on cellular functions and mechanisms.